Do utopian city designs from the social reform literature of the seventeenth and nineteenth centuries resonate with a modern audience? - Morrison, Tessa; Rubin, Mark (Journal of Architecture and Urbanism, 2016)
Utopian cities from social reform literature from the seventeenth and nineteenth centuries were a serious attempt to improve living and working conditions of their time. Some of this literature included a design for a city that would be complimentary to and enhance the political philosophy of the respective authors. Four of the most famous works which include a plan of a city are, Tommaso Campanella’s Civitas Solis (City of the Sun) (1602), Johann Valentin Andreae’s Christianopolis (1619), Robert Owen’s Villages of Co-operation (1817 & 1830) and James Silk Buckingham’s Victoria (1849). These works are frequently featured in literature on utopian cities. However, no consideration is given to whether these ‘utopian’ cities have any value as urban plans or whether they incorporate any desirable urban features. These urban designs of the city are significant to political philosophies because the cities are presented as being integral to such philosophies. This paper considers the following questions: ‘Do the main principles behind the initial political philosophies and their coinciding plan endure within the design of these cities?’ ‘Does a modern audience perceive in these cities the features that made them utopian in the centuries in which they were planned?’